Do corpo político à política do corpo: teatro,memória e ideologia na obra do ator e teatrólogo Ademir Faleiros entre as décadas de 1980 e 1990 - Melo , Moisés de Oliveira (2023)
This study is an extension of the course completion work presented at the end of the 2020 academic year at the State University of Goiás, under the title "Ademir Faleiros in the Theater Scene of Anápolis: An Analysis of the Plays "Favela Brasil" and "Por Detrás de Toda Porta"". In this sense, the object of this dissertation is to study part of the playwright's life and work. Through the intrinsic relationship between history and literature, the aim is to understand the theatrical scene in Anápolis during the 1980s and 1990s. This includes highlighting the social, economic, and political aspects that marked the last decade of the Brazilian civil-military dictatorship, the influence of censorship and repression mechanisms on the development and presentation of the author's plays throughout the state of Goiás, as well as his dramaturgical writing. It also seeks to understand the role of engaged theater in a city like Anápolis and the choir as an ideological agent in the staging of the play "Favela Brasil" (1980). It also examines the social function of theater at the time of the political opening and how the beginning of the country's re-democratization influenced the author's writing in plays such as "Por Detrás de Toda Porta" (1989). Finally, it highlights the relevance of the study for the historiography of Goiás theater, as well as Ademir Faleiros' legacy for the theater scene in the city of Anápolis.